2015
DOI: 10.1007/s10310-015-0496-z
|View full text |Cite
|
Sign up to set email alerts
|

Leaf traits suggest different ecological strategies for twoQuercusspecies along an altitudinal gradient in the Qinling Mountains

Abstract: Local-scale study on leaf traits and their relationships in a single species along an environmental gradient is essential for scaling up ecophysiological processes from the leaf to the ecosystem level. Here, we quantified 25 leaf traits of two individual species, Quercus aliena var. acutiserrata (Qa, deciduous) and Quercus spinosa (Qs, evergreen), in the same genus, but with different life-form to investigate the leaf traits and relationship variations within and between species along an altitudinal gradient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
2
8
1
Order By: Relevance
“…We found that the leaves of plants became thicker, the leaf area became smaller, the photosynthesis ability was stronger, and their ability to retain nutrients became stronger in the special environment of high temperature. This was consistent with the existing research results [16,19]. These traits together form the global leaf economics spectrum, reflecting the different ecological strategies that plants use to balance the cost and effort of leaf construction costs.…”
Section: Relationship Between Functional Traits Of Plant Leaves and Tsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the leaves of plants became thicker, the leaf area became smaller, the photosynthesis ability was stronger, and their ability to retain nutrients became stronger in the special environment of high temperature. This was consistent with the existing research results [16,19]. These traits together form the global leaf economics spectrum, reflecting the different ecological strategies that plants use to balance the cost and effort of leaf construction costs.…”
Section: Relationship Between Functional Traits Of Plant Leaves and Tsupporting
confidence: 90%
“…In the long-term adaptation of the living environment, plants gradually form a series of morphological and physiological structural traits that are interrelated, coevolving and adapt to changes in the external environment, collectively referred to as plant functional traits [15,16]. Moreover, plants often respond to environmental changes by adjusting their functional traits [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…According to Stojnić et al (2016), physiological parameters are influenced by environmental conditions of sites and genetic constitution of proveniences or populations. Altitudinal effects on photosynthesis of different proveniences or populations were elucidated by Chai et al (2015), Benavides et al (2016), Ran et al (2013), Pšidová et al (2017). Effects of slope are poorly investigated as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf development trait serves as a model for plant developmental exibility [Reich 2014]. Studies of leaf traits could greatly improve our understanding of leaf function and plant performance [Blackman et al2016;Chai et al 2015]. In our study, the change of leaf area and leaf thickness was increased (Table 2), this result should be closely related to the anatomical observation of leaves.…”
Section: Discussionmentioning
confidence: 49%